Peculiarities of the Relationship between Higher Education and Poverty in the RA - Harutyunyan, Karine (Bulletin of Yerevan University G: Economics, 2022)
This article presents the results of the study on the interrelation between higher education and poverty and their peculiarities in Armenia. The analysis of the data on the student body in the higher education institutions clearly shows that the number of students from different social strata of the population is very different, in particular, the number of students from poor families is much smaller than from wealthy ones. Moreover, the analysis shows that in recent years there has been a decrease in the proportion of not only fee- paying students but also students who pay no fees, which is a very worrying trend. Moreover, the comparison of tuition fees with the poverty line in Armenia makes it clear that almost half of the households cannot afford to have a student on a paid basis, as the average tuition fee is more than their monthly consumption expenditure. Thus, higher education in Armenia is essentially unaffordable for poor families, which is a result of the lack of a state policy aimed at ensuring social justice and equal access to higher education.